The effect of reducing welfare access on employment, health, and children's long-run outcomes - Jeffrey Hicks; Gaëlle Simard-Duplain; David A. Green; William Warburton (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2022)
How does welfare affect the prosperity of mothers and their children? We study this question using a Canadian welfare reform and by linking administrative welfare records to tax returns, nearly all medical spending, and children's educational attainment. Eighty percent of mothers in the complier group found employment within a year, and for many, total income rose despite reduced transfers. We find precise zero effects on total health expenditures for both mothers and children. However, composition changes, including fewer family physician visits, indicate that mothers had less time to seek health care. We find precise zero effects on children's test scores and graduation, but modest reductions of intergenerational transmission of welfare.
Keywords: H23; H31; I38; 330; welfare; health; public